Framework for Client-Server Distributed Database System for Federal Road Safety Commission Nigeria - Tuperekiye E., Sese (Advances in Social Sciences Research Journal, 2020)
In recent years it has been observed that the federal road safety commission FRSC has been having some challenges on how to handle traffic rule and traffic offences committed by road users both commercial and private. Based on the in ability of the FRSC to handle these problems this paper critically looked into the behavioural pattern of the drivers towards traffic rules and offences committed and found that there was a great need for the Organisation to have a good database, that will be able to keep records of traffic offences and offenders, which can be called upon at any time on reference basis. The aim of this study is to create a distributed Federal Road Safety commission traffic offence system that can access data from any state of the Federation. The system consists of a relational database of FRSC variables which could be shared by the various States and Local Government Areas in the country. Each of the local government area will form a website, and the database will be hosted by the server at the Federal Road Safety Commission Head Quarters at Abuja and at the various state capital. . All LGAs will access the database via a distributed network. The client/server distributed network architecture is used in the design and implementation of the system. The system is capable of monitoring all road offences and traffic offenders records at all levelsfrom any part of the country and generation of reports concerning offenders and also access information from the local government at all times.